MORPHOMETRIC AND MOLECULAR VARIATION OF NEON TETRA FISH (Paracheirodon innesi) FROM BOJONGSARI DISTRICT, INDONESIA - Musthofa, Siti Zuhriyyah; Alimuddin, Alimuddin; Arfah, Harton; Sulistyowati, Dinar Tri; Carman, Odang; Kusrini, Eni (Indonesian Aquaculture Journal, 2024)
Neon tetra, Paracheirodon innesi, is endemic to rivers and streams in southeastern Colombia, eastern Peru, and western Brazil and is commercially traded as aquarium fish in the world. In Indonesia, neon tetras were mass produced in Bojongsari District, Depok, West Java as the centre of neon tetra fish production. Understanding their genetic variation is useful for implementing their selective breeding programs, environmental restoration, and estimating genetic contributions in stocks. The current study aimed to investigate the patterns of morphometric and molecular diversity using randomly amplified polymorphic DNA-polymerase chain reaction techniques among farmed broodstocks of P. innesi in Indonesia. Three populations, namely: the Bojongsari, Curug, and Pondok Petir derived from the Bojongsari District, Depok, west Java, were used in the study. Thirty live fish from each location were analyzed based on 25 truss morphometric characters. Sixty fresh fish samples were obtained for DNA analysis using the RAPD-PCR technique, which uses three random primers. Principal component analysis (PCA) was performed to distinguish morphometric variations among populations. Morphological and molecular analysis displayed a similar result that Bojongsari and Pondok Petir neon tetra fish had high similarities, while Curug neon tetra was distinguished from others. The closest genetic distance was between the Pondok Petir and Curug populations (0.4088), while the farthest genetic distance was between the Curug and Bojongsari populations (0.4138). The results will be useful in developing breeding programs to improve broodstock quality.